Influence of vesicle curvature on fluorescence relaxation kinetics of fluorophores - Hof, M; Hutterer, R; Pérez, N; Ruf, H; Schneider, F W (Biophysical chemistry, 1994)
The effect of membrane curvature on the fluorescence decay of 2-p-toluidinyl-naphthalene-6-sulfonic acid (TNS), 2-(9-anthroyloxy) stearic acid (2-AS) and 12-(9-anthroyloxy)-stearic acid (12-AS) was investigated for egg lecithin vesicles of average diameter dm = 22 nm and 250 nm. The biexponential fluorescence decay of TNS at the red edge of the emission spectrum was analysed according to the model of Gonzalo and Montoro [1]. Over the entire temperature range (1-40 degrees C) the small TNS labelled vesicles showed significantly shorter solvent relaxation times tau(r) than their larger counterparts (e.g. 1.3 ns compared with 2.1 ns at 5 degrees C), indicating a higher mobility of the hydrated headgroups in the highly curved, small vesicles. The fluorescence decay of both AS derivatives is also biexponential. While the shorter decay times (1-3 ns) are practically identical for small and large vesicles, the longer decay times (5-14 ns) are identical only for 12-AS but not for 2-AS. This indicates that the microenvironment is similar in small and large vesicles deep in the membrane in spite of the differences in curvature.